Envenenamento experimental por Bothrops jararaca em camundongos prenhes: Eficácia do soro antibotrópico - Ferreira, Karla Vanessa [UNIFESP] (2011)
Introduction: Snakebite accidents are considered a rare event among pregnant women, but serotherapy is indicated even when envenomation is not severe. However, antivenom can cause maternal adverse reactions and consequently fetal death. Experimental Bothrops jararaca (Bj) envenomation can provoke marked morphological alterations in the antimesometrial (AM) region of uterus in pregnant mice which can culminate in the end of gestation. This investigation aimed to verify whether Bothrops antivenom (BAV) could restore the normal morphology of murine uterus, after Bj envenomation. Methods: On the morning of day 7,5 of pregnancy, animals received Bj venom (0.24mg Bj venom/kg body weight) i.m., and after 3 hours they were treated with BAV i.v. (VBj+BAV). Control groups received saline and was treated with BAV (Sal+BAV) or Bj venom (VBj). On day 8,5, uterine morphology was analyzed, especially at the maternal-fetal interface in the AM region. Plasma fibrinogen (Fg) was assayed in plasma samples of pregnant animals. Aiming to study the external appearance and the skeletal morphology of fetuses, as well as the incidence of fetal resorptions, another group of animals on day 7,5 received the same treatments mentioned and was sacrificed on day 18,5. Results: Histological analysis of most dams of the VBj group revealed the maternal and fetal tissues disorganized, showing hemorrhagic areas and a prominent inflammatory infiltrate at the maternal-fetal interface. Additionally, decidual cells (maternal) and trophoblastic giant cells (fetal) exhibited evident signs of necrosis. The antimesometrial decidua of most dams of the VBj+BAV revealed the maternal fetal tissues organized, similarly to the uteri of dams of the Sal+BAV group. Analyses of the external appearance and skeletal morphology of fetuses on day 18,5 showed no difference among groups; however, the dams that received Sal+BAV and were treated with ABS showed smaller fetuses than VBj+BAV group. Plasma Fg levels of the VBj+BAV group were similar to those of Sal+BAV group. However, experimental Bj envenomation showed lower plasma Fg levels. Conclusion: Our results indicated that the treatment with the antibothropic serum was capable to maintain the development of the gestation, preserving the morphology in the maternal-fetal interface, in the animals.